Incorporating traditional Negeri Sembilan architecture in modern buildings: a case study of the Seremban District Administration Office - Mohd Nor, Othman; Muhammad, Afzanizam; Mohd Isa, Haryati; Abdul Halim, Nurrajwani; Abdul Karim, Norashikin (2025)
Every region in the world has distinctive architecture or monuments that serve as iconic representations of its identity. In Malaysia, Negeri Sembilan is renowned for its unique architectural style. This study aims to identify the traditional architectural characteristics of Negeri Sembilan that have been integrated into modern government administrative buildings, focusing on the Seremban District Administration Office in the capital city. The research methodology includes field observations and expert interviews. The findings reveal that key traditional elements can indeed be successfully incorporated into modern structures. The Old Seri Menanti Palace was used as a reference in this project. This study is significant because it contributes to the development of general guidelines for future projects of a similar nature. The conclusion drawn from the research is that the Seremban District Administration Office reflects traditional architectural characteristics, making it an iconic structure in Negeri Sembilan. The study demonstrates that traditional architectural features can be integrated into modern buildings, even when contemporary materials and technologies are used. This research serves as a benchmark and provides guidelines for future projects aiming to blend traditional and modern architectural elements.